2018
DOI: 10.1002/pip.3032
|View full text |Cite
|
Sign up to set email alerts
|

Alkali treatments of Cu(In,Ga)Se2 thin‐film absorbers and their impact on transport barriers

Abstract: We study the impact of different alkali post‐deposition treatments by thermal admittance spectroscopy and temperature‐dependent current‐voltage (IVT) characteristics of high‐efficiency Cu(In,Ga)Se2 thin‐film solar cells fabricated from low‐temperature and high‐temperature co‐evaporated absorbers. Capacitance steps observed by admittance spectroscopy for all samples agree with the widely observed N1 signature and show a clear correlation to a transport barrier evident from IVT characteristics measured in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 46 publications
7
68
0
Order By: Relevance
“…(B1) and, thus, the absolute conductance, might differ by up to 2 orders of magnitude between different devices. Furthermore, these values are likely specific to the buffer layers deposited in our lab, since, for example, in a recent study we reported a thermally activated behavior for devices fabricated at different institutes [20]. For the temperature-dependent conductance of the p-n junction also shown in Fig.…”
Section: Appendix B: Temperature-dependent Buffer Conductancementioning
confidence: 72%
See 1 more Smart Citation
“…(B1) and, thus, the absolute conductance, might differ by up to 2 orders of magnitude between different devices. Furthermore, these values are likely specific to the buffer layers deposited in our lab, since, for example, in a recent study we reported a thermally activated behavior for devices fabricated at different institutes [20]. For the temperature-dependent conductance of the p-n junction also shown in Fig.…”
Section: Appendix B: Temperature-dependent Buffer Conductancementioning
confidence: 72%
“…Primarily, it has been attributed to a defect, although conflicting evidence exists concerning where these defects are located within the device [9,11,12]. This standard interpretation was recently challenged by an increasing number of publications which suggest alternative explanations for the N1 level, mostly linked to the transport characteristics of the solar-cell absorber [13,14] or to a transport barrier [7,[15][16][17][18][19][20][21] within the device.…”
Section: Introductionmentioning
confidence: 99%
“…[27] To extract the drop in capacitance and the activation energy of the capacitance step, the fitting method proposed by Weiss et al is applied to the capacitance spectra. [28] The activation energies of the main capacitance step show a good correlation to the incorporated Rb amount as depicted in Figure 7a. Consequently, a good correlation to the low-temperature activation energy from the differential resistance is obtained as represented in Figure 7b.…”
Section: Injection Barrier Formationmentioning
confidence: 75%
“…The forward‐bias dark current densities were found to follow a simple diode model without signatures for interface barriers for all 3 devices. This indicates that the main admittance step is not related to a barrier but to shallow defects. Based on the activation energies of step 2, it can be observed that the activation energy of the main capacitance step decreases from 135 to 115 to 90 meV with the addition of Ga.…”
Section: Performance and Defect Analysismentioning
confidence: 95%
“…For CIS_0.95, a double step could be observed with activation energies of 40 and 135 meV. To confirm whether this capacitance step is indeed related to a defect signature or a barrier, the extracted activation energies were compared to the temperature dependences of series resistance and dark diode current from IVT measurements …”
Section: Performance and Defect Analysismentioning
confidence: 99%